Congenital Melanotic Macules of the Tongue: Case Report and Literature Review - Kim, Kang Hyuk; Cho, Jung Woo; Jung, Seung Hwan; Kim, Jin Su; Park, Je Uk; Kim, Chang Hyen (The Korean Journal of Oral and Maxillofacial Pathology, 2016)
Oral hyperpigmentation is common in patients older 40 years. But lesions in a newborn are unusual and congenital melanotic macule of the tongue has rarely been reported. A 2-month-old infant with 3 pigmented lesion on the right side of the dorsal tongue was evaluated. They were brown black but not homogeneous in color, smooth, nonblanchable, and nonpalpable, with irregular margins. We recommend excisional biopsy under general anesthesia because of possibility of malignancy, but parents refuse invasive procedure. On a following-up examination of the child at the age of 1 year, the pigmented lesions were unchanged. We report a case of congenital melanotic macules on the tongue and a review of literature about the lesion. KCI Citation Count: 0